In vitro toxicological characterisation of arsenic-containing fatty acids and three of their metabolites. Issue 5 (3rd July 2015) - Meyer, S.; Raber, G.; Ebert, F.; Leffers, L.; Müller, S. M.; Taleshi, M. S.; Francesconi, K. A.; Schwerdtle, T.
Graphical Abstract: Abstract: Arsenic-containing fatty acids are a group of fat-soluble arsenic species (arsenolipids) which are present in marine fish and other seafood. Recently, it has been shown that arsenic-containing hydrocarbons, another group of arsenolipids, exert toxicity in similar concentrations comparable to arsenite although the toxic modes of action differ. Hence, a risk assessment of arsenolipids is urgently needed. In this study the cellular toxicity of a saturated (AsFA 362) and an unsaturated (AsFA 388) arsenic-containing fatty acid and three of their proposed metabolites (DMA V, DMAPr and thio-DMAPr) were investigated in human liver cells (HepG2). Even though both arsenic-containing fatty acids were less toxic as compared to arsenic-containing hydrocarbons and arsenite, significant effects were observable at μM concentrations. DMA V causes effects in a similar concentration range and it could be seen that it is metabolised to its highly toxic thio analogue thio-DMA V in HepG2 cells. Nevertheless, DMAPr and thio-DMAPr did not exert any cytotoxicity. In summary, our data indicate that risks to human health related to the presence of arsenic-containing fatty acids in marine food cannot be excluded. This stresses the need for a full in vitro and in vivo toxicological characterisation of these arsenolipids.